Return to Sports and Physical Activity After Total and Unicondylar Knee Arthroplasty: A Systematic Review and Meta-Analysis - Witjes, Suzanne; Gouttebarge, Vincent; Kuijer, P. Paul F. M.; van Geenen, Rutger C. I.; Poolman, Rudolf W.; Kerkhoffs, Gino M. M. J. (Sports medicine (Auckland), 2016)
Background People today are living longer and want to remain active. While obesity is becoming an epidemic, the number of patients suffering from osteoarthritis (OA) is expected to grow exponentially in the coming decades. Patients with OA of the knee are progressively being restricted in their activities. Since a knee arthroplasty (KA) is a well accepted, cost-effective intervention to relieve pain, restore function and improve health-related quality of life, indications are expanding to younger and more active patients. However, evidence concerning return to sports (RTS) and physical activity (PA) after KA is sparse. Objectives Our aim was to systematically summarise the available literature concerning the extent to which patients can RTS and be physically active after total (TKA) and unicondylar knee arthroplasty (UKA), as well as the time it takes. Methods PRISMA guidelines were followed and our study protocol was published online at PROSPERO under registration number CRD42014009370. Based on the keywords (and synonyms of) ‘arthroplasty’, ‘sports’ and ‘recovery of function’, the databases MEDLINE, Embase and SPORTDiscus up to January 5, 2015 were searched. Articles concerning TKA or UKA patients who recovered their sporting capacity, or intended to, were included and were rated by outcomes of our interest. Methodological quality was assessed using Quality in Prognosis Studies (QUIPS) and data extraction was performed using a standardised extraction form, both conducted by two independent investigators. Results Out of 1115 hits, 18 original studies were included. According to QUIPS, three studies had a low risk of bias. Overall RTS varied from 36 to 89 % after TKA and from 75 to >100 % after UKA. The meta-analysis revealed that participation in sports seems more likely after UKA than after TKA, with mean numbers of sports per patient postoperatively of 1.1–4.6 after UKA and 0.2–1.0 after TKA. PA level was higher after UKA than after TKA, but a trend towards lower-impact sports was shown after both TKA and UKA. Mean time to RTS after TKA and UKA was 13 and 12 weeks, respectively, concerning low-impact types of sports in more than 90 % of cases. Conclusions Low- and higher-impact sports after both TKA and UKA are possible, but it is clear that more patients RTS (including higher-impact types of sports) after UKA than after TKA. However, the overall quality of included studies was limited, mainly because confounding factors were inadequately taken into account in most studies.